226 ECHOCARDIOGRAPHIC AND INVASIVE EVALUATION OF LEFT ATRIAL PRESSURE IN PATIENTS UNDERGOING CATHETER ABLATION FOR ATRIAL FIBRILLATION. (15th December 2022) - Bonelli, Andrea; Inciardi, Riccardo Maria; Cersosimo, Angelica; Dell´era, Gabriele; Degiovanni, Anna; Spinoni, Enrico; Bosco, Manuel; Arabia, Gianmarco; Salghetti, Francesca; Bellicini, Mariagiulia; Brangi, Elisa; Legati, Michele; et al.
Abstract: Aims: Estimation of left ventricle (LV) filling pressure is one of the most important parameters to provide information in clinical practice. However, the challenging in investigating this parameter through invasive methods makes it difficult to be used. The study aims to investigate the association between cardiac structure and function derived by transthoracic echocardiography (TTE) and left atrial (LA) invasive pressure (LAP). Methods: The study was a multi-center prospective study enrolling 73 patients (mean age 65 ± 8, 27% female) undergoing primary catheter ablation for AF. Patients were evaluated and enrolled from June 2021 to April 2022. Complete TTE assessing measures of LV, LA and right ventricle (RV) structure and function including speckle tracking echocardiography, was performed at baseline. Echocardiographic data have been assessed the same day of the invasive measurement of the LAP during AF ablative procedure. Linear regression analysis has been performed to assess the relationship between measures of cardiac structure and function and LAP. Logistic regression analysis assessed the parameters associated with elevated LAP (≥ 15mmHg). Results: Baseline clinical characteristics of the study population did not differ according to elevated LAP vs. non-elevated LAP. Patients with elevated LAP showed instead abnormal measures of LV global longitudinal strain, measures of LA structure and function, except for LA maximal volume, and RV structure and function. After multivariable adjustment, including demographic factors and comorbidities, E/e`(p = 0, 024), LA minimal volume (p = 0, 009), LA emptying fraction (LAEF) (p = 0, 012), LA Reservoir (p = 0, 039), TAPSE (p = 0, 010) and RV free wall strain (p = 0, 028), but not LA maximal volume (p = 0, 11), were significantly associated with LAP. Similarly, these measures, but nor LA maximal volume, were significant determinants of elevated LAP. Overall, LA minimal volume and LAEF showed the best diagnostic accuracy to predict elevated LAP (AUC 0.72 and 0.73, respectively). Conclusions: Novel measures of LA structure and function, but not standard assessment by LA maximal volume, were significantly associated with LAP in patients affected by AF. These measures, along with measures of LV and RV function may be used in the diagnostic assessment of filling pressure in ambulatory settings.